2018
DOI: 10.1021/acs.jpcc.7b06673
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Properties of Two-Dimensional Organic–inorganic Halide Perovskites and their Stability against Moisture

Abstract: Organic–inorganic halide perovskites have attracted increasing interest for solar-energy harvesting because of the simple fabrication process, high efficiency, and low cost. In this work, we systematically investigate the structural and electronic properties, and stability of two-dimensional (2D) hybrid organic–inorganic perovskites (HOIPs) based on density-functional-theory calculations. We explore a general rule to predict the bandgap of the 2D HOIP: its bandgap decreases as the thickness increases and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
(84 reference statements)
1
12
0
Order By: Relevance
“…The structural flexibility and tunability as well as the significant quantum confinement effects of the low dimension perovskites provide a rich and fertile "playground" for the prepa-ration of interesting crystal structures with various properties predicted by calculations, such as tunable bandgap, Rashba band splitting, and high stability against moisture, oxygen, and heat. [97][98][99][100][101] As shown in Figure 2, the 2D (C 4 H 9 NH 3 ) 2 PbX 4 (X = Cl, Br, and I) hybrid perovskites showed the layer dependent properties. [102] For example, the effect mass of hole m h * increases in proportion to the decreased layer thickness, the absorption peaks redshift from 502 nm for the single layer to 519 nm for the sextuple layer, and converge at 522 nm for bulk (C 4 H 9 NH 3 ) 2 PbI 4 .…”
Section: Low Dimensional Perovskitesmentioning
confidence: 99%
“…The structural flexibility and tunability as well as the significant quantum confinement effects of the low dimension perovskites provide a rich and fertile "playground" for the prepa-ration of interesting crystal structures with various properties predicted by calculations, such as tunable bandgap, Rashba band splitting, and high stability against moisture, oxygen, and heat. [97][98][99][100][101] As shown in Figure 2, the 2D (C 4 H 9 NH 3 ) 2 PbX 4 (X = Cl, Br, and I) hybrid perovskites showed the layer dependent properties. [102] For example, the effect mass of hole m h * increases in proportion to the decreased layer thickness, the absorption peaks redshift from 502 nm for the single layer to 519 nm for the sextuple layer, and converge at 522 nm for bulk (C 4 H 9 NH 3 ) 2 PbI 4 .…”
Section: Low Dimensional Perovskitesmentioning
confidence: 99%
“…The 2D-HOIPs with different phases (tetragonal and orthorhombic) can be obtained due to the orientation of C–N bonds with the MA cations. Our previous study demonstrated that the 2D tetragonal phase with the parallel (TETP) structure of the C-N bonds shows the highest efficiency for solar-to-power conversion [40]. Therefore, in this study, we focus on the TETP structures with three inorganic sheets ( n = 3) of 2D-HOIPs, including SnI-2D-HOIPs, PbI-2D-HOIPs, SnBr-2D-HOIPs and PbBr-2D-HOIPs.…”
Section: Resultsmentioning
confidence: 99%
“…We focus on the SnI-2D-HOIPs mixed with different composition ratios of the Cs, Rb, Ge and Pb atoms. The energy for molecule adsorption (E a ) can be calculated as follows [40]:Ea=Em/SESEm where E m/S , E S , and E m are the energies of the mixed 2D-HOIP with molecule, the 2D-HOIPs, and the molecule, respectively. If E a is negative, the slab surface is an easy to adsorb molecule, while the surface is repulsive if the energy is positive.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, after electrons and holes are generated, they can recombine quickly, which lowers the performance of catalysts. 17 Various strategies have been developed to tackle these challenges. Z-scheme photocatalytic systems that used two connecting photocatalysts were a potential approach for improving photocatalytic activity, and their photocatalytic activity was superior to that of single-component photocatalysts.…”
Section: Introductionmentioning
confidence: 99%